Content Analysis of Da'wah Messages in Hadrah Art Verses (Case Study of Hadrah Art in Parado District, Bima Regency, West Nusa Tenggara Province) - Ahmad Farid; Nur Hidayat Muh. Said; Ramsiah Tasruddin (STKIP Taman Siswa Bima, 2025)
This research discusses the message of da'wah in the Hadrah art poetry in Parado District, Bima Regency, West Nusa Tenggara Province (analysis of the contents of the da'wah message). This research is classified as qualitative research with a type of library research or library. Researchers try to collect data by analyzing several articles, journals or books related to the research theme. Data analyzed begins by collecting data and then reducing data, namely selecting, grouping and disposing of unnecessary data, then displaying data or data presentation, finally conducting data verification, and if there is incomplete data, it will be added. SWT., The command of faith in the angel of Allah, the command of faith in the books of Allah, and the command of faith in the Prophet and Apostle. Second, the Islamic message consists of: an order to maintain a relationship with Allah SWT., And the command to hold fast to the law. Third, moral messages consist of: Morals to Allah SWT., And morals to the Prophet.